PENGARUH KARAKTERISTIK INDIVIDU, KARAKTERISTIK PEKERJAAN DAN KOMPENSASI TERHADAP MOTIVASI KERJA KARYAWAN PT. BANK RAKYAT INDONESIA CABANG PURWOKERTO - Burhanudin burhanudin; P. Edi Sumantri; Mayla Surveyandini (Majalah Imiah Manajemen & Bisnis, 2017)
This research entitled "The Influence of Individual Characteristics, Job Characteristics and Compensation on Work Motivation of Employees of PT. Bank Rakyat Indonesia Purwokerto Branch ". The purpose of this study was to determine the significance of the influence of individual characteristic variables on the work motivation of employees of PT. Bank Rakyat Indonesia Purwokerto Branch, to determine the significance of the influence of job characteristics variables on work motivation of PT. Bank Rakyat Indonesia Purwokerto Branch and to find out the significance of the effect of compensation variables on work motivation of PT. Bank Rakyat Indonesia Purwokerto Branch. The analysis uses multiple linear regression. From this research it can be concluded: Individual characteristics have a significant influence on work motivation of employees of PT. Bank Rakyat Indonesia Purwokerto Branch. Job characteristics have a significant influence on work motivation of employees of PT. Bank Rakyat Indonesia Purwokerto Branch. Compensation have a significant influence on work motivation of employees of PT. Bank Rakyat Indonesia Purwokerto Branch